Enhancing Community Awareness on Halal Product Certification in Rural Yogyakarta: A Legal and Practical Intervention - Gunawan, Yordan (Borobudur Journal on Legal Services, 2025)
This community service program aims to increase public awareness and business owners' understanding of the importance of halal product certification through legal and practical approaches in Dusun Ngringin and Dusun Pragak, Semanu District, Gunung Kidul Regency. Halal certification is key to ensuring product quality and compliance with Islamic law, as well as opening up broader market opportunities. The program was carried out through counseling, dissemination, and practical assistance on the halal certification process. The results indicate a significant increase in participants' understanding of the procedures and benefits of halal certification. Furthermore, business owners showed enthusiasm to begin the halal certification process, although challenges related to cost and administrative procedures remain. This program contributes to local economic development and empowering small and medium enterprises (SMEs) by improving the quality of halal products, thereby opening up opportunities in both domestic and international markets.